Human dental pulp mesenchymal stem cells regenerative potential - Fadiyan Amriel, Menza; Priyo Prasetyo, Eric; Auzan Fepiosandi, Radixtio; Agustin Wahjuningrum, Dian; Suardita, Ketut; Zora, Zofia; Natan, Daniel; Bin Zainal Abidin, Imran; Ohara, Masaru (Universitas Airlangga, 2025)
Background: Stem cells can be divided into mono-potent, oligopotent, multipotent, pluripotent, and totipotent. Dental and oral stem cells are stem cells found in the teeth and mouth that has the potential to develop into various cell types. The rapid development of regenerative dentistry has resulted in the exploration of stem cells, including dental pulp mesenchymal stem cells. Mesenchymal stem cells, have important regenerative potential in repairing dental and surrounding tissues. One of dental stem cells source that have been discovered is dental pulp mesenchymal stem cells. Purpose: This article aims to review the regenerative potential of human dental pulp mesenchymal stem cells (HDPMSCs). Review: HDPMSCs are potential for regenerative dentistry, including regenerative endodontics due to their multipotency, ease of collection, and ability to support tissue repair, immunomodulation, and regeneration across dental, orthopedic, neurological, and cardiovascular applications. Conclusion: The regenerative potentials of HDPMSCs on various treatments are vastly explored by many studies.